1999
DOI: 10.1016/s0929-1393(98)00157-7
|View full text |Cite
|
Sign up to set email alerts
|

Response of Faba bean (Vicia faba L.) to combined inoculation with Azotobacter and Rhizobium leguminosarum bv. viceae

Abstract: Mixed inoculation of the grain legume faba bean (Vicia faba L.) with Rhizobium leguminosarum bv. viceae strain Z25 and ®ve different Azotobacter chroococcum or A. vinelandii strains, under gnotobiotic conditions of culture, resulted in signi®cant effects on nodulation, plant growth and nitrogenase activity (acetylene-reduction activity, ARA) of nodulated roots at thē owering stage. A. chroococcum strain H23 and A. vinelandii strains ATCC 12837 and Dv42 promoted plant growth, signi®cantly increasing dry matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
2
19
0
3
Order By: Relevance
“…In pot experiments conducted under gnotobiotic conditions or with the use of sterile soils [Burns et al 1981, El-Bahrawy 1983, Rodelas et al, 1999 it has been shown that nodulation intensity, efficiency of nitrogen fixation and yields of some legumes inoculated with mixed cultures of rhizobia and other beneficial microorganisms, like Azotobacter spp. and Azospirillum spp., were higher as compared to those inoculated with the rhizobia alone.…”
Section: Resultsmentioning
confidence: 99%
“…In pot experiments conducted under gnotobiotic conditions or with the use of sterile soils [Burns et al 1981, El-Bahrawy 1983, Rodelas et al, 1999 it has been shown that nodulation intensity, efficiency of nitrogen fixation and yields of some legumes inoculated with mixed cultures of rhizobia and other beneficial microorganisms, like Azotobacter spp. and Azospirillum spp., were higher as compared to those inoculated with the rhizobia alone.…”
Section: Resultsmentioning
confidence: 99%
“…Root attachment and colonization constitute an important stage, and little is known about their mechanisms. A. vinelandii has been known to be a good plant growth-promoting bacterium (2,4). In this study, the response of A. vinelandii to association with the roots of O. sativa was examined under different growth medium conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known to be a plant growth-promoting bacterium capable of fixing nitrogen and forming desiccation-resistant cysts under unfavorable growth condition (1,2). The former activity requires it to house several oxygen-sensitive mechanisms while being an obligate aerobic bacterium (3).…”
mentioning
confidence: 99%
“…Both strains are vitamin producers in media amended with 0Á5% glucose, and have shown growth-promoting ability on plants (Martõ Ânez-Toledo et al 1988a, b;Rodelas et al 1999).…”
Section: Strainsmentioning
confidence: 99%